2013
DOI: 10.2478/s11687-013-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

The risk to human health related to disposal of animal wastes to soil — microbiological and parasitical aspects

Abstract: SummaryThe study was conducted to investigate the microbiological and parasitical risk related to the disposal of animal manure to soil by storage of raw pig slurry at temperatures 4°C, 20 °C and 42 °C for 115 days. Plate counts of Salmonella typhimurium and number of devitalized non-embryonated model Ascaris suum eggs were determined on days 0, 7, 12, 22, 32, 40, 55, 90 and 115 of storage. At the same intervals level of selected physico-chemical parameters were determined. Microbiological examination showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In turn, Olszewska et al [12] noted that in pig slurry stored for 44 weeks (the same time as in Katakam's research) under laboratory conditions at 4 °C the percentage of invasive eggs of Ascaris suum decreased to a level of 49 %, while in pig slurry stored at 20 °C to 11 %. The study of Kachnic et al [65] also showed that at higher temperatures devitalization of Ascaris suum eggs was increased, however, even after 115 days of raw slurry storage at 42 °C, complete devitalization was not achieved. An excessive fertilizing use of pig slurry in fields and pastures or the application of slurry from sick animals, including asymptomatic ones, can be a source of microbial contamination of soils (due to the impairment of self-purifying ability) and plants, which in turn poses a risk of pathogens infiltrating into the food chain of animals (domestic and wild) and humans [62,64,71].…”
Section: Microbiological Contamination Of the Environmentmentioning
confidence: 97%
See 1 more Smart Citation
“…In turn, Olszewska et al [12] noted that in pig slurry stored for 44 weeks (the same time as in Katakam's research) under laboratory conditions at 4 °C the percentage of invasive eggs of Ascaris suum decreased to a level of 49 %, while in pig slurry stored at 20 °C to 11 %. The study of Kachnic et al [65] also showed that at higher temperatures devitalization of Ascaris suum eggs was increased, however, even after 115 days of raw slurry storage at 42 °C, complete devitalization was not achieved. An excessive fertilizing use of pig slurry in fields and pastures or the application of slurry from sick animals, including asymptomatic ones, can be a source of microbial contamination of soils (due to the impairment of self-purifying ability) and plants, which in turn poses a risk of pathogens infiltrating into the food chain of animals (domestic and wild) and humans [62,64,71].…”
Section: Microbiological Contamination Of the Environmentmentioning
confidence: 97%
“…Bacteria in pig slurry can survive for many days (Table 2), according to Olszewska and Skowron [64] bacilli of Salmonella Typhimurium are able to survive in the slurry stored in laboratory conditions at 4 °C for about 75 days while at 20 °C their survival time is shorter and amounts 30 days. However, Kachnic et al [65] noted that Salmonella Typhimurium survived in the pig slurry (stored in closed plastic containers) for less than 115 days at 4 °C and less than 90 days at 20 °C and 42 °C. Ajariyakhajorn et al [66] observed that Salmonella Anatum survived in the pig slurry, the pH of which was equal to 7.0, for 56 days at 4 °C.…”
Section: Microbiological Contamination Of the Environmentmentioning
confidence: 99%
“…For comparison, in the present experiment this percentage after 6, 10 and 18 weeks was equal to 50 %, 73 % and 61 % at 20 °C and 79 %, 88 % and 79 % at 4 °C, respectively. Kachnič et al (2014) Johnson et al (1998) observed that both temperature and the part of lagoon have the effect on the level of invasive eggs elimination. According to the results of their study in the period between 5 and 25 week of the experiment the percentage of A. suum live eggs in the middle part of the lagoon decreased from 77 % to 11 %, and in the outflow from 68 % to 48 % (Johnson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Men who owned dogs also adopted a greater number of PEBs. Several authors 11,54,55 identified a positive association between these variables and did not differentiate them according to gender.…”
Section: Pro-environmental Behaviors: Relationship With Other Analyze...mentioning
confidence: 99%